Using mind mapping to help students at Thanh Hoa College of Agriculture and Forestry recycle vocabulary = Sử dụng sơ đồ tư duy để giúp sinh viên ở Trường Trung cấp Nông Lâm Thanh Hóa tái sử dụng từ vựng. M.A Thesis Linguistics: 60 14 10 - Lưu, Văn Hậu (University of Languages and International Studies, 2017)
M.A. Thesis. English Linguistics Teaching Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013